The fragrant companions : a play about love between women - Li, Yu, 1611-1680? (Translations from the Asian classics., 2022)
"Written in 1651, The Fragrant Companions is the first of ten extant chuanqi plays by Li Yu. The play, told in 36 acts, is one of the only literary works of pre-modern China that focuses on the theme of lesbian love. The play tells the story of two young ladies of the gentry who fall in love with each other after exchanging poems in a nunnery and overcome different obstacles to be together through a recognized marriage-by marrying the same husband. While its finale of a heterosexual marriage seems to reconcile with the Confucian gender ideology, polygamy, and the patriarchal social order, the play is really about the two women's genuine love and passion for each other; their mutual longing when separated; their efforts and resourcefulness to surmount social bias and impediments; and the triumph of their love over social mandates and expectations"--